Diaphragm-coated MOFs glass in-situ polymerization solid electrolyte, and preparation method and application thereof
By coating MOFs glass on the separator and performing in-situ polymerization, a separator-coated MOFs glass in-situ polymerization solid electrolyte is formed, which solves the problems of low ionic conductivity and poor interface compatibility of polymer solid electrolytes at room temperature, and achieves higher ionic conductivity and mechanical strength.
Patent Information
- Application Number
- CN202411443559.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-16
- Publication Date
- 2025-01-24
AI Technical Summary
Polymer solid electrolytes have low ionic conductivity and poor interfacial compatibility at room temperature, limiting their use in industrial applications.
By coating MOFs glass on the separator and performing in-situ polymerization, a separator-coated MOFs glass in-situ polymerization solid electrolyte is formed to improve its ionic conductivity and mechanical strength.
It significantly enhances the polymer ion conductivity, enhances the mechanical strength of the composite solid electrolytes and the ability to suppress the metal branches, improves the interface contact, and solves the problem of poor low -electrical guidance and interface compatibility in existing technologies.
Smart Images

Figure CN119361799A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of composite solid electrolytes, in particular to a diaphragm-coated MOFs glass in-situ polymerized solid electrolyte and a preparation method and application thereof. Background Art
[0002] Polymer solid electrolytes have the advantages of good flexibility and high safety, and are expected to replace traditional flammable and explosive organic liquid electrolytes. However, the low ionic conductivity and poor interface compatibility at room temperature severely limit their industrial application. Therefore, improving their ionic conductivity and improving their interface compatibility are important directions for the development of polymer solid electrolytes. Introducing inorganic fillers into polymers is one of the effective ways to improve the ionic conductivity and interface stability of polymer electrolytes. This is mainly based on (1) the introduction of inorganic fillers can reduce the crystallinity of polymers and accelerate ion conduction; (2) inorganic fillers form a new interface layer with polymers, which provides additional ion transmission channels; (3) inorganic fillers can improve the mechanical strength of polymer electrolytes and enhance the ability to inhibit metal dendrites.
[0003] As a new type of inorganic material, the glassy metal-organic framework has the characteristic of no grain boundary, which significantly reduces the resistance of ion transmission, promotes uniform ion deposition isotropically, and inhibits the growth of dendrites, thereby improving the battery rate performance and safety. In-situ polymerization can fill the gaps between the solid electrolyte and the electrode; it can also fill the gaps between the glassy metal-organic framework particles, significantly improving the interface contact between the composite solid electrolyte and the electrode, and improving the ion transmission of the composite solid electrolyte.
[0004] Therefore, the diaphragm is used as a support, MOFs glass is coated and monomers are polymerized in situ on the diaphragm to obtain a composite solid electrolyte with good mechanical strength, strong metal dendrite suppression ability, high ionic conductivity and good interface contact. To this end, a diaphragm-coated MOFs glass in situ polymerization solid electrolyte and its preparation method and application are proposed. Summary of the invention
[0005] The purpose of the present invention is to provide a diaphragm-coated MOFs glass in-situ polymerized solid electrolyte and a preparation method and application thereof, so as to solve the problems raised in the above-mentioned background technology.
[0006] To achieve the above object, the present invention provides the following technical solution: a diaphragm coated with MOFs glass in-situ polymerized solid electrolyte, comprising polymer monomers and MOFs glass;
[0007] MOFs glass powder, binder and solvent are mixed in proportion and coated on both sides of the membrane. After drying, a membrane coated with MOFs glass is obtained. Then, a certain concentration of polymer monomers, metal salts and initiator solutions are added to the membrane coated with MOFs glass. Under thermal or photoinitiation conditions, the monomers inside the battery are in situ polymerized on the MOFs glass membrane to obtain a membrane-coated MOFs glass in-situ polymerized solid electrolyte.
[0008] Preferably, the polymer monomer includes but is not limited to acrylates, modified acrylates (such as ethyl cyanoacrylate, fluorinated acrylates), cyclic carbonates, cyclic ethers (such as 1,3-dioxolane, 1,3,5-trioxane), acrylamide, ethyleneimine, isocyanate and polyol monomers or at least one thereof;
[0009] Preferably, the types of MOFs glass include but are not limited to phosphate-imidazole series (such as [Zn(HPO4)(H2PO4)](H2Im)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3]H(2-MebIm), [Zn3(H2PO4)6(H2O)3](BTA) etc.), zeolite imidazole salt series (such as ZIF-7, ZIF-8, ZIF-62, ZIF-76 etc.), titanium oxide cluster-hydroquinone series (such as Ti 16 O 16 (OEt) 32 、Ti 12 O 16 (O-iPr) 16 etc.), thiocyanates (such as Cu2(SCN)3(C4bpy), [Co(μ-NCS)2(C5H5N3O)2]·C5H5N3O) and bis(fluorosulfonyl)imide-nitrile framework series (such as Li[N(SO2F)2](NCCH2CH2CN)2), metal-bis(acetamide) framework (such as Co(hmba)3[Co(NCS)4], Co(bba)3[CoCl4], Co(hmba)3[CoBr4]), carboxylic acid metal-organic framework (such as UiO-67, UiO-68, DUT-5, [Mg4(adipate)4(DMA)(H2O),) pyridine-carboxylic acid metal-organic framework (such as [Mn3(peb)6]·2DMF) or at least one of them.
[0010] Preferably, the solid electrolyte is a diaphragm-coated MOFs glass in-situ polymerized solid electrolyte.
[0011] Preferably, the polymer monomer content in the solid electrolyte is 40-99.5wt%, the MOFs glass content in the solid electrolyte is 0.01-50wt%, the metal salt content in the solid electrolyte is 0.1-40wt%, and the initiator content in the solid electrolyte is 0.1-5wt%.
[0012] The preparation method of the diaphragm-coated glassy metal organic framework in-situ polymerized composite solid electrolyte further comprises the following steps:
[0013] 1. Dissolve the binder in the solvent to form a mixed solution of a certain concentration, and then mix the MOFs glass powder and the binder in a certain proportion;
[0014] 2. Apply the mixed solution after ball milling to the diaphragm. After the solvent evaporates and dries, a diaphragm coated with MOFs glass of a certain thickness is obtained;
[0015] 3. Dissolve the polymer monomer, metal salt, initiator or interfacial layer formation promoter in the polymer monomer or solvent to prepare a mixed solution of a certain concentration;
[0016] 4. During the battery assembly process, the prepared mixed solution is added to the diaphragm coated with MOFs glass. Under thermal or photoinduced conditions, the monomers inside the battery are polymerized in situ to form an in-situ composite solid electrolyte membrane coated with MOFs glass.
[0017] Preferably, in step 1, the ratio of MOFs glass powder to binder is 6 to 12:1, in step 2, the thickness of the composite solid electrolyte is 1 to 100 μm, and in step 3, the concentration of the metal salt is 0.1 to 4 mol L -1 , the mass of the initiator is 0.1-5wt% of the mass of the monomer, in step 4, the polymerization conditions are 40-100°C, and the time is 2-24h.
[0018] Preferably, the positive electrode, the negative electrode and the diaphragm are coated with MOFs glass in-situ polymerized solid electrolyte membrane, and the battery structure is a button type, soft pack, cylindrical or square shell battery; the metal salt includes but is not limited to perchlorate, tetrafluoroborate, hexafluorophosphate, bisoxalate borate, difluorooxalate borate, bisdifluorosulfonyl imide salt, bistrifluoromethylsulfonyl imide salt, nitrate, sulfate and trifluoromethanesulfonate, etc.; the cation in the above metal salt includes any one of Li ion, Na ion, Mg ion, Ca ion, K ion, Zn ion, Al ion or proton. Different types of cations correspond to corresponding types of solid-state batteries, and the solid-state battery is a positive electrode, a negative electrode and a MOFs glass / polymer solid electrolyte between the positive and negative electrodes.
[0019] Preferably, when the cation is a Li ion, it can be a solid-state lithium battery. Specifically, the solid-state lithium battery in the present application refers to a solid-state battery whose carrier is a lithium ion, such as a solid-state lithium-sulfur battery, a solid-state lithium-air battery, a solid-state lithium-oxygen battery, a solid-state lithium-carbon dioxide battery, a solid-state lithium-ion battery, a solid-state lithium metal battery, etc.
[0020] When the cation is a Na ion, it can be a solid-state sodium battery.
[0021] When the cation is Mg ion, it can be a solid-state magnesium battery.
[0022] When the cation is a Ca ion, it can be a solid-state calcium battery.
[0023] When the cation is K ion, it can be a solid-state potassium battery.
[0024] When the cation is a Zn ion, it can be a solid-state zinc battery.
[0025] When the cation is an Al ion, it can be a solid-state aluminum battery.
[0026] When the cation is a proton, it can be a solid-state fuel cell.
[0027] In this application, the solid-state sodium battery, solid-state magnesium battery, solid-state calcium battery, solid-state potassium battery, solid-state zinc battery, and solid-state aluminum battery are similar to the solid-state lithium battery and will not be described in detail here.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The membrane-coated MOFs glass in-situ polymerized solid electrolyte in the present invention significantly improves the polymer ion conductivity and enhances the mechanical strength of the composite solid electrolyte, thereby improving the metal dendrite inhibition capability, solving the problems of poor interface contact, poor ion conductivity, and low mechanical strength of the existing polymer solid electrolyte.
[0030] 2. The membrane-coated MOFs glass in-situ polymerized solid electrolyte of the present invention has good air stability, high chemical stability, and is cheap and easy to process, and is easy to mass produce, store and transport. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] Figure 1 This is a constant current charge and discharge performance diagram of the diaphragm-coated MOFs glass in-situ polymerized solid electrolyte prepared by the present invention at 25°C and 2C;
[0032] Figure 2 Symmetrical cells assembled with MOFs glass in-situ polymerized solid electrolytes prepared by the present invention at 25°C and 0.1 mA cm -2Plot of long cycles at different current densities. DETAILED DESCRIPTION
[0033] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0034] Embodiment 1
[0035] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0036] The preparation process is:
[0037] (1) After the glassy ZIF-7 is refined, the powder and the binder are evenly mixed in a ratio of 6:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0038] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 25 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0039] (3) Dissolve 1 g of polymer monomer in a 1 M metal salt solution containing 1 wt % of initiator and mix well.
[0040] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0041] (5) The battery assembled in step (4) was allowed to stand for 3 h, and then placed in an oven at 40° C. for 4 h to allow in-situ polymerization to occur.
[0042] The MOFs glass in-situ polymerization solid-state battery obtained in Example 1 was subjected to electrochemical performance testing at 25°C and a current density of 2C. The electrochemical performance of the symmetric battery and the full battery was measured as follows: Figure 1 and Figure 2 shown.
[0043] Embodiment 2
[0044] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0045] The preparation process is:
[0046] (1) After glassy Zn(HPO4)(H2PO4)](H2Im)2 is refined, its powder is evenly mixed with a binder in a ratio of 8:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0047] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 20 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0048] (3) Dissolve 1 g of polymer monomer in a 1.5 M metal salt solution containing 2 wt % of initiator and mix well.
[0049] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0050] (5) The battery assembled in step (4) was allowed to stand for 2 h, and then placed in an oven at 60° C. for 8 h to allow in-situ polymerization to occur.
[0051] Embodiment 3
[0052] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0053] The preparation process is:
[0054] (1) Glassy Ti 12 O 16 (O-iPr) 16 After being refined, the powder is evenly mixed with a binder in a ratio of 9:1, and a certain amount of solvent is added thereto to obtain a slurry.
[0055] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 25 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0056] (3) Dissolve 1 g of polymer monomer in a 1 M metal salt solution containing 0.5 wt % of initiator and mix well.
[0057] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0058] (5) The battery assembled in step (4) was allowed to stand for 1 hour and then placed in an oven at 70° C. for 4 hours to allow in-situ polymerization to occur.
[0059] Embodiment 4
[0060] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0061] The preparation process is:
[0062] (1) After the glassy Cu2(SCN)3(C4bpy) is refined, its powder is evenly mixed with a binder in a ratio of 10:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0063] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 35 μm, dried for 10 hours, and cut into a solid electrolyte membrane of a required size.
[0064] (3) Dissolve 1 g of polymer monomer in a 2 M metal salt solution containing 2 wt % of initiator and mix well.
[0065] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0066] (5) The battery assembled in step (4) was allowed to stand for 3 hours and then placed in an oven at 80° C. for 4 hours to allow in-situ polymerization to occur.
[0067] Embodiment 5
[0068] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0069] The preparation process is:
[0070] (1) After the glassy DUT-5 is refined, the powder and the binder are evenly mixed in a ratio of 12:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0071] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 15 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0072] (3) Dissolve 1 g of polymer monomer in a 2.5 M metal salt solution containing 1.5 wt % of initiator and mix well.
[0073] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0074] (5) The battery assembled in step (4) is placed in an oven at 90°C for 6 hours to allow in-situ polymerization to occur.
[0075] Embodiment 6
[0076] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0077] The preparation process is:
[0078] (1) After the glassy [Mn3(peb)6]·2DMF is refined, its powder is evenly mixed with a binder in a ratio of 8:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0079] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 10 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0080] (3) Dissolve 1 g of polymer monomer in a 3 M metal salt solution containing 1 wt % of initiator and mix well.
[0081] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0082] (5) The battery assembled in step (4) was placed in an oven at 70°C for 6 hours to allow in-situ polymerization to occur.
[0083] Embodiment 7
[0084] The preparation process is:
[0085] (1) After the glassy Co(bba)3[CoCl4] is refined, the powder and the binder are evenly mixed in a ratio of 10:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0086] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 20 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0087] (3) Dissolve 1 g of polymer monomer in a 1 M metal salt solution containing 2 wt % of initiator and mix well.
[0088] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0089] (5) The battery assembled in step (4) was placed in an oven at 80°C for 4 hours to allow in-situ polymerization to occur.
[0090] Embodiment 8
[0091] Diaphragm coated MOFs glass in-situ polymerization solid electrolyte and preparation method
[0092] The preparation process is:
[0093] (1) After glassy Li[N(SO2F)2](NCCH2CH2CN)2 is refined, the powder and the binder are evenly mixed in a ratio of 9:1, and a certain amount of solvent is added to obtain a slurry after mixing.
[0094] (2) The slurry obtained in step (1) is coated on both sides of the separator with a thickness of 15 μm, dried for 10 hours, and cut into solid electrolyte membranes of required sizes.
[0095] (3) Dissolve 1 g of polymer monomer in a 1 M metal salt solution containing 2 wt % of initiator and mix well.
[0096] (4) Assembling button-type, soft-pack, cylindrical or square-shell batteries with the solid electrolyte membrane obtained in step (2) and the mixed solution obtained in step (3) in the order of negative electrode, solid electrolyte membrane, a certain amount of mixed solution and positive electrode.
[0097] (5) The battery assembled in step (4) was allowed to stand for 1 hour and then placed in an oven at 60° C. for 8 hours to allow in-situ polymerization to occur.
[0098] It should be noted that, in this article, relational terms such as first and second, etc. are only used to distinguish one entity or operation from another entity or operation, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Moreover, the terms "include", "comprise" or any other variants thereof are intended to cover non-exclusive inclusion, so that a process, method, article or device including a series of elements includes not only those elements, but also other elements not explicitly listed, or also includes elements inherent to such process, method, article or device.
[0099] Although embodiments of the present invention have been shown and described, it will be appreciated by those skilled in the art that various changes, modifications, substitutions and variations may be made to the embodiments without departing from the principles and spirit of the present invention, and that the scope of the present invention is defined by the appended claims and their equivalents.
Claims
1. A diaphragm-coated MOFs glass in-situ polymerized solid electrolyte, comprising a polymer monomer, MOFs glass, a metal salt and a binder, characterized in that: MOFs glass powder, binder and solvent are mixed in proportion and then coated on both sides of the diaphragm, and the diaphragm coated with MOFs glass is obtained after drying, and then a certain concentration of polymer monomer, metal salt and initiator solution are added to the diaphragm coated with MOFs glass, and the monomers inside the battery are in situ polymerized on the MOFs glass diaphragm under thermal initiation or photoinitiation conditions, so that the diaphragm coated with MOFs glass in situ polymerized solid electrolyte can be obtained; in: A. Glassy metal-organic frameworks can be obtained by heat treatment, mechanical ball milling, mechanical pressure, and X-ray irradiation; B. MOFs glass coated on the diaphragm as inorganic filler for solid electrolyte; C. The metal salt is dissolved in the polymer monomer or solvent; D. The polymer is obtained by in-situ polymerization of monomers under thermal or photoinduced conditions after the battery is assembled; E. A solid electrolyte interface layer (SEI / CEI) formation promoter may or may not be added to the composite solid electrolyte.
2. The diaphragm-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The polymer monomers include, but are not limited to, acrylates, modified acrylates (such as ethyl cyanoacrylate, fluorinated acrylates), cyclic carbonates, cyclic ethers (such as 1,3-dioxolane, 1,3,5-trioxane), acrylamide, ethyleneimine, isocyanate and polyol monomers or at least one of them.
3. The membrane-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The MOFs glass includes but is not limited to phosphate-imidazole series (such as [Zn(HPO4)(H2PO4)](H2Im)2, [Zn3(H2PO4)6(H2O)3](HbIm), [Zn3(H2PO4)6(H2O)3]H(2-MebIm), [Zn3(H2PO4)6(H2O)3](BTA) etc.), zeolite imidazole salt series (such as ZIF-7, ZIF-8, ZIF-62, ZIF-76 etc.), titanium oxide cluster-hydroquinone series (such as Ti 16 O 16 (OEt) 32 、Ti 12 O 16 (O-iPr) 16 etc.), thiocyanates (such as Cu2(SCN)3(C4bpy), [Co(μ-NCS)2(C5H5N3O)2]·C5H5N3O) and bis(fluorosulfonyl)imide-nitrile framework series (such as Li[N(SO2F)2](NCCH2CH2CN)2), metal-bis(acetamide) framework (such as Co(hmba)3[Co(NCS)4], Co(bba)3[CoCl4], Co(hmba)3[CoBr4]), carboxylic acid metal-organic framework (such as UiO-67, UiO-68, DUT-5, [Mg4(adipate)4(DMA)(H2O),) pyridine-carboxylic acid metal-organic framework (such as [Mn3(peb)6]·2DMF) or at least one of them.
4. The diaphragm-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The MOFs glass is obtained by, but not limited to, grinding, ball milling, melt-quenching, mechanical pressure or X-ray irradiation.
5. The diaphragm-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The metal salts include but are not limited to perchlorates, tetrafluoroborate, hexafluorophosphate, bis(oxalatoborate), difluorooxalatoborate, bis(difluorosulfonylimide), bis(trifluoromethylsulfonylimide), nitrates, sulfates and trifluoromethanesulfonates, etc. The cations in the above metal salts include any one of Li ions, Na ions, Mg ions, Ca ions, K ions, Zn ions, Al ions or protons.
6. The membrane-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The thermal initiator and the photoinitiator include but are not limited to azobisisobutyronitrile, peroxide, hexafluorophosphate, trifluoromethanesulfonate, tetrafluoroborate and stannous isooctanoate, and the binder includes but is not limited to polypyrrole, polyvinylidene fluoride, polyaniline, carboxymethyl cellulose, styrene-butadiene rubber latex, polytetrafluoroethylene and alginate, etc.
7. The membrane-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The content of polymer monomer in the solid electrolyte is 40-99.5wt%, the content of MOFs glass in the solid electrolyte is 0.01-50wt%, the content of metal salt in the solid electrolyte is 0.1-40wt%, and the content of initiator in the solid electrolyte is 0.1-5wt%.
8. The membrane-coated MOFs glass in-situ polymerized solid electrolyte according to claim 1, characterized in that: The solid interface layer formation promoter includes but is not limited to nitrate, fluoride, fluoroethylene carbonate and difluorooxalate borate, and the separator includes but is not limited to polyethylene, polypropylene, polyacrylonitrile, polyimide, cellulose membrane and glass fiber membrane.
9. A method for preparing a diaphragm-coated MOFs glass in-situ polymerized solid electrolyte, characterized in that: The preparation method also includes the following steps: S1. Dispersing MOFs glass powder and binder in a solvent in a certain proportion and mixing them to form a mixed slurry of a certain concentration; S2, coating the slurry on the diaphragm, and after the solvent evaporates and dries, a diaphragm coated with MOFs glass of a certain thickness is obtained; S3, dissolving polymer monomers, metal salts, initiators or interfacial layer formation promoters in polymer monomers or solvents to prepare a mixed solution of a certain concentration; S4. Assemble button-type, soft-pack, cylindrical or square-shell batteries according to the structural layout of the negative electrode, MOFs glass solid electrolyte membrane and the positive electrode, add the prepared mixed solution to the diaphragm coated with MOFs glass, and polymerize the monomers added inside the battery in situ under thermal or photoinitiation to form a diaphragm-coated MOFs glass in-situ polymerized solid electrolyte membrane.
10. A solid-state energy storage device having the above solid-state electrolyte, characterized in that: The positive electrode, the negative electrode and the diaphragm are coated with a MOFs glass in-situ polymerized solid electrolyte membrane, and the battery structure is a button-type, soft-pack, cylindrical or square-shell battery.
Citation Information
Cited By
Molybdenum disulfide / polyether-based in-situ composite solid electrolyte as well as preparation method and application thereof
CN120048986A
Preparation method and application of in-situ curing solid electrolyte based on porous base membrane
CN121054793A
Sodium ion solid electrolyte and preparation method and application thereof
CN121076239A